The scientific and intellectual impact of the family of Musa bin Shakir During the Abbasid era (198-265 AH/813-879AD) - عباس, رندة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
During the era of translation, which flourished in the Umayyad era and reached its climax in the Abbasid era, the Islamic community witnessed the existence of scientific families that contributed an important role in transferring many of the sciences of other nations to the Islamic world. Not only vector minds, but creative and productive minds that were able to pave the way for those who came after them. Among these families is the Musa bin Shaker family, which lived in the third century AH / ninth century AD, and influenced political and scientific events, as their encyclopedic culture enabled them to lay the foundations of the scientific edifice that attracted the attention of the Caliphs of Banu al-Abbas to them, after their fame in various sciences such as mathematics, astronomy and stars that were It had a distinguished presence in the era of the Caliph al-Ma’mun, who embraced and nurtured them scientifically, literary and socially, so they formed a major place in the history of science in general and technology in particular,This study aims to shed light on what this family left of scientific material and a civilized legacy related to the scientific and intellectual aspect, and the extent of its contributions in the various fields of science. About the most important sciences for which they were famous and through which their great role in wisdom emerged. The study also showed their most important scientific products.